Makna Komunikasi Keluarga dalam Video Klip Hindia “ Secukupnya” - Rizaldy; O. Hasbiansyah (Bandung Conference Series: Communication Management, 2022)
Abstract. Hindia video clip entitled “Sufficiently” The video clip uploaded on the Sun Eater youtube channel on May 3, 2019 shows texts that have stories, most of these texts are related to family matters. this video clip has been viewed by 4,954,475 people to date. Therefore, the researcher is interested in researching the meaning of family communication in the Indies Video Clip "as needed"(semiotic analysis of the text of the meaning of family communication in the Indian video clip "as needed" ) by doing hermeneutic reading of texts and text hypograms. Researchers used qualitative research methods with Michael Riffattere's Semiotics approach. The results of this study show (semiotic analysis of the text of the meaning of family communication in the Indian video clip "as needed" Using the qualitative research method with Michael Riffattere's semiotic approach. The result of this research is communication describes the feeling of distress, filled with regret, disappointed, sad, happy mingled into one packed with the familiar faces with an unhappy and facial expression. Video represent the events and the current, where family communication forms in culture has the same case, resulting in a lack of creates happiness for children from their parents Abstrak. Video klip Hindia yang berjudul “Secukupnya” Video klip yang di unggah di kanal youtube Sun Eater pada tanggal 3 Mei 2019 memperlihatkan teks-teks yang memiliki cerita, kebanyakan tek-teks ini berhubungan dengan masalah keluarga. video klip ini telah dilihat oleh 4.954.475 orang hingga saat ini. Oleh karena itu, peneliti tertarik untuk meneliti Makna Komunikasi Keluarga dalam Video Klip Hindia “Secukupnya” (Analisis Semiotika teks Makna Komunikasi Keluarga dalam Video Klip Hindia “Secukupnya”) dengan melakukan pembacaan hermeunetik teks dan hipogram teks. Peneliti menggunakan metode penelitian Kualitatif dengan pendekatan Semiotika Michael Riffattere. Hasil dari penelitian ini menunjukan komunikasi keluarga yang menggambarkan anak merasa tertekan, penuh dengan penyesalan, kecewa, sedih, bahagia bercampur menjadi satu dikemas dengan cerita yang pilu dengan raut wajah dan ekspresi wajah yang tidak bahagia. Video merepresentasikan pesan peristiwa dan fenomena yang terjadi saat ini, di mana bentukan komunikasi keluarga secara budaya mempunyai kasus yang sama, yang berdampak pada kurangnya menciptakan kebahagiaan bagi anak dari orang tuanya.